The Short-Term Economic Consequences of COVID-19: Exposure to Disease, Remote Work and Government Response - Louis-Philippe Béland; Abel Brodeur; Taylor Wright (Institute of Labor Economics (IZA), 2020)
In this ongoing project, we examine the short-term consequences of COVID-19 on employment and wages in the United States. Guided by a pre-analysis plan, we document the impact of COVID-19 at the national-level using a simple difference and test whether states with relatively more confirmed cases/deaths were more affected. Our findings suggest that COVID-19 increased the unemployment rate, decreased hours of work and labor force participation and had no significant impacts on wages. The negative impacts on labor market outcomes are larger for men, younger workers, Hispanics and less-educated workers. This suggest that COVID-19 increases labor market inequalities. We also investigate whether the economic consequences of this pandemic were larger for certain occupations. We built three indexes using ACS and O*NET data: workers relatively more exposed to disease, workers that work with proximity to coworkers and workers who can easily work remotely. Our estimates suggest that individuals in occupations working in proximity to others are more affected while occupations able to work remotely are less affected. We also find that occupations classifed as more exposed to disease are less affected, possibly due to the large number of essential workers in these occupations.
Keywords: I15; I18; J21; 330; COVID-19; unemployment; wages; remote work; exposure to disease